Baleenopelta rotunda, a newly discovered limpet from decaying baleen from New Zealand. (2nd January 2021) - Marshall, Bruce A.; Walton, Kerry
ABSTRACT: A new genus and species of the Osteopeltidae that is restricted to decaying baleen is described from 377 to 1042 m depth off mainland New Zealand, the Chatham Islands and the Auckland Islands. ZooBank registration : urn:lsid:zoobank.org:pub:4CD02E01-9B34-405B-B6CC-D4306C81A690